Impact of coronavirus disease (COVID‐19) on HIV testing and care provision across four continents. Issue 2 (10th October 2021) - Rick, Fernanda; Odoke, Wilfred; van den Hombergh, Jan; Benzaken, Adele S.; Avelino‐Silva, Vivian I.
Abstract: Objectives: The coronavirus disease (COVID‐19) pandemic has been associated with severe disruptions in health care services, and nonpharmacological measures such as social distancing also have an impact on access to screening tests and on the long‐term care of patients with chronic conditions globally. We aimed to describe the impact of the COVID‐19 pandemic on HIV testing and treatment and to describe strategies employed to mitigate the impact of COVID‐19 on HIV care. Methods: In this retrospective cohort study, we used secondary data from the AIDS Healthcare Foundation (AHF) Global Quality Program from 44 countries in four continents (Asia, Latin America and the Caribbean, Europe and Africa), and compared information on HIV testing, percentage of positive results, number of in‐person appointments, and number of new enrolments in HIV care from 1 January 2020 to 31 August 2020 with the equivalent period in 2019. Results: Despite marked inter‐country heterogeneities, we found that COVID‐19 was associated with a significant reduction in HIV testing, an increase in the percentage of positive tests, a reduction in the number of in‐person consultations and a reduction in the number of new enrolments in care, despite the implementation of several mitigation strategies. The impact of COVID‐19 differed across continents and key populations. Conclusions: Our findings suggest that, in the years to come, health care services must be prepared to respond to the impact of COVID‐19 on HIV testing and care. Providers and facilities should build on the lessons learned so far to further improve mitigation strategies and establish care priorities for both the pandemic and the post‐pandemic periods.